SYSTEM FOR SHIFT OPTIMIZATION THROUGH COGNITIVE FATIGUE: AN INNOVATIVE APPROACH IN INDUSTRIAL ENGINEERING: SYSTEM FOR SHIFT OPTIMIZATION THROUGH COGNITIVE FATIGUE: AN INNOVATIVE APPROACH IN INDUSTRIAL ENGINEERING - Yankova-Yordanova, Yordanka (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This paper presents an innovative system for workforce scheduling and optimization that integrates quantitative analysis of operators’ cognitive fatigue. Traditional scheduling models focus on staff availability and minimum task coverage while neglecting the dynamic nature of the human factor [12]. The proposed method utilizes data from behavioral and biometric sensors, combined with machine learning algorithms, to predict the onset of critical cognitive fatigue. This enables proactive and dynamic redistribution of tasks and breaks to minimize human error, enhance safety [3], and maintain consistently high productivity levels. Simulation study results demonstrate a significant reduction in error risk compared to standard rotational schedules.